Analysis of locus D9S1120 and its genetic admixture correlation in seven argentina native american ethnic groups. Issue 1 (19th June 2015) - Caputo, Mariela; Corach, Daniel
Abstract : Objective: Genetic data have complemented archaeological and linguistic investigations for understanding the peopling of the Americas. Aiming to investigate the Native South American genetic background in Argentina, seven Amerindian and one urban population were selected. The analysis focused on locus D9S1120 due to its potential anthropological information about Native American origins. Methods: The sample set included 603 individuals belonging to nine isolated Argentinean aboriginal communities from seven tribes ( N  = 296), 100 individuals living in Buenos Aires city, and three potentially parental population references samples ( N  = 207). We computed allele and genotype frequency distributions, genetic distances, and pairwise differences among and within them. Admixture proportion was determined by means of typing 13 autosomal short tandem repeats plus D9S1120 in all populations, and comparing the data with those from three parental groups including Native American, European and Sub Saharan West African. Results: The Native American‐specific allele 9RA was found at an average frequency of 0.26 in aboriginal groups. Statistically significant differences were observed among the Native American groups when compared with the Buenos Aires urban population using analysis of molecular variance (AMOVA) ( F st  = 0.05669; P  < 0.0001). Admixture analysis denoted different results between the cohorts of Amerindian samples displaying the specific 9RA allele, compared with those lacking it. A linear correlation was established between positive 9RA and Native American ancestry. Conclusions: Autosomal‐based genetic admixture showed that the studied communities have considerable European and Native America contributions. Our results concerning D9S1120 further contribute to a better understanding of the admixture process between Sub Saharan African, Native American, and European individuals that shaped the genetic background of Argentinean extant population. Am. J. Hum. Biol. 28:57–66, 2016. © 2015 Wiley Periodicals, Inc.